ChemInform Abstract: Catalytic, Asymmetric, and Stereodivergent Synthesis of Non‐symmetric β, β‐Diaryl‐α‐Amino Acids. Issue 26 (June 2015) - Molinaro, Carmela; Scott, Jeremy P.; Shevlin, Michael; Wise, Christopher; Menard, Alain; Gibb, Andrew; Junker, Ellyn M.; Lieberman, David
Abstract Stereodefined enol tosylates such as (III) and (VI) are prepared and subjected to a stereoretentive Suzuki—Miyaura coupling.